Masticatory performance in patients undergoing free fibula flap for mandible reconstruction - Jun Zhang; Yujing Wang; Lulu Yuan; Weiren Wang (BMC, 2022)
Abstract Background To explore the masticatory performance in patients undergoing an osteo(cutaneous) free fibula (OFF) flap for mandible reconstruction by a prospective design. Methods A total of 56 patients who had undergone OFF flap reconstructions for mandibular reconstruction secondary to malignant (squamous cell carcinoma) or benign (ameloblastoma) tumor resection were prospectively enrolled. They were asked to complete the masticatory performance test by the weigh method and the chew domain of the University of Washington quality of life questionnaire (version 4) preoperatively and at 3, 6, and 12 months postoperatively. The pair nonparametric test was used to analyze the dynamic change of masticatory performance and subjective chew function. Results Fifty-one patients were included for analysis finally. The mean masticatory performance for patients with malignant tumors were 53.4% ± 10.3%, 36.4% ± 10.3%, 42.6% ± 9.6%, 52.8% ± 10.9%, and 53.1% ± 11.8% preoperatively, at 2 weeks, 3 months, 6 months, and 12 months postoperatively, respectively. Compared with the preoperative level, the masticatory performance had a significant reduction immediately after surgery (p < 0.001), followed by a return to the baseline level within three months. A similar trend was noted for those with benign tumors. The mean score of chew domain for patients with malignant tumors were 100 ± 0, 54.3 ± 32.9, 81.4 ± 24.5, and 92.9 ± 17.8 preoperatively, at 3 months, 6 months, and 12 months postoperatively, respectively. Compared with the preoperative level, the subjective chew function was greatly affected within the first three months (p < 0.001), and it gradually recovered to the baseline level in the following nine months. A similar trend was noted in patients with benign tumors. Conclusions The masticatory performance and subjective chew function was significantly affected after OFF flap reconstructions in the short term, but both recovered to the preoperative levels within 9-12 months.